1995
DOI: 10.1007/bf00665943
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tumor derived fibroblasts and 1,25-dihydroxyvitamin D3 on growth of breast cancer cell lines

Abstract: Fibroblasts are known to be present in variable amounts in human breast adenocarcinoma tissue. In order to investigate if they influence in some way the proliferation rate of the carcinoma cells, we developed a coculture model in which cells of well characterized breast epithelial cell lines were seeded and grown in microchamber slides along with fibroblasts derived from breast tumor biopsies. As representatives of hormone dependent and independent tumor cells, we used MCF-7 and BT-20 cell lines. A third line,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
6

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 14 publications
1
14
1
6
Order By: Relevance
“…Fibroblasts were also able to stimulate BT-20 cell line growth that was significantly higher than the proliferative response observed for the MCF-7 cell line. Growth stimulation of BT-20 ceils by fibroblasts derived from breast tumor biopsies has also been observed in direct cocuhure by Lefebvre et al (1995). However, in contrast to our results, the level of the proliferative response was similar in BT-20 and MCF-7 cell lines.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Fibroblasts were also able to stimulate BT-20 cell line growth that was significantly higher than the proliferative response observed for the MCF-7 cell line. Growth stimulation of BT-20 ceils by fibroblasts derived from breast tumor biopsies has also been observed in direct cocuhure by Lefebvre et al (1995). However, in contrast to our results, the level of the proliferative response was similar in BT-20 and MCF-7 cell lines.…”
Section: Discussioncontrasting
confidence: 86%
“…Conversely, Hofland et al (1995) described recently growth stimulation of MCF-7 carcinoma cells by normal human foreskin fibroblasts when cocultured in permeable tissue-culture systems. Lefebvre et al (1995), using a monolayer coculture system, demonstrated that fibroblasts derived from breast tumor biopsies were able to stimulate the proliferation of carcinoma cell lines. Finally, van Roozendaal et al (1992van Roozendaal et al ( , 1996 demonstrated that conditioned serum-free media produced by breast fibroblasts in primary culture were able to stimulate the proliferation of a variety of breast carcinoma cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…c : & t b l . growth factors produced by stromal fibroblasts have been shown to stimulate the growth of breast cancer cells [17] and the invasiveness of scirrhous gastric cancer cells [14]. Many growth factors also have angiogenetic effects in cancer tissue [27].…”
Section: Discussionmentioning
confidence: 99%
“…The role of fibroblasts in tumor proliferation is unclear. Tumor-derived fibroblasts have been described as stimulating tumor cell progression of different breast cancer cell lines, 33,34 whereas fibroblasts from healthy breast tissue inhibited tumor cell growth of MCF-7 cells. 35 However, there is abundant evidence that host tissue cells such as fibroblasts do actively participate in malignant invasion upon the production of soluble factors, different cytokines, proteolytic enzymes and/or components of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%